Effect of Position and Number of Hydroxyl Groups on the Oscillatory Behaviour of Isomers of Hydroxybenzoic Acid - Masood A. Nath; Nadeem B. Ganaie; R. P. Rastogi; G. M. Peerzada (E-Journal of Chemistry)
In the present communication, the effect of isomers of hydroxybenzoic acids with respect to their oscillatory behaviour as organic substrates with inorganic bromate and manganese(II) ion as catalyst in aqueous acid medium (1.0 M H2SO4) have been studied. The number and the relative position of hydroxyl groups (-OH) in the aromatic ring is found to influence the oscillatory behaviour. Besides, the role of bromination reaction and the formation of corresponding bromoderivative is found to be an important step. The experimental findings are within the purview of Field, Koros and Noyes (FKN) mechanism.